Penggunaan Aplikasi Canva Pada Pembuatan Media Pembelajaran Di Taman Kanak-kanak (TK) - Marlina, Dwi; Primawati, Alusyanti; Niswati, Za’imatun; Deanova, Ilham (Kapas: Kumpulan Artikel Pengabdian Masyarakat, 2024)
Since the start of distance learning (PJJ), teachers have been required to create interactive learning media using computers. One of the applications that supports creating interesting learning media using computers, namely the Canva application. The Canva application has many features and functions that can help in creating learning media. The obstacle faced by teaching staff, especially teachers, is the lack of skills in using the Canva application to create learning media. This was experienced by kindergarten teachers who were not used to using the Canva application. Some of the obstacles that are often encountered are not understanding how to use the features in Canva to design media. This is the background for the PKM team to provide training with the theme “Pembuatan Media Pembelajaran pada Pendidikan Anak Usia Dini (PAUD) dengan Aplikasi Canva”. The result of this activity is to improve participants' skills and understanding regarding the use of the Canva application.